Water repellency reduces soil CO2 efflux upon rewetting - Carmen Sanchez-Garcia (Science of The Total Environment, 2020)
Carbon dioxide (CO2) efflux from soil represents one of the biggest ecosystem carbon (C) fluxes and high-magnitude pulses caused by rainfall make a substantial contribution to the overall C emissions. It is widely accepted that the drier the soil, the larger the CO2 pulses will be, but this notion has never been tested for water-repellent soils. Soil water repellency (SWR) is a common feature of many soils and is especially prominent after dry periods or fires. An important unanswered question is to what degree SWR affects common assumptions about soil CO2 dynamics. To address this, our study investigates, for the first time, the effect of SWR on the CO2 pulse upon wetting for water-repellent soils from recently burned forest sites. CO2 efflux measurements in response to simulated wetting were conducted both under laboratory and in situ conditions. Experiments were conducted on strongly and extremely water-repellent soils, with a wettable scenario simulated by adding a wetting agent to the water. CO2 efflux upon rewetting was significantly lower in the water-repellent scenarios. Under laboratory conditions, CO2 pulse was up to four times lower under the water-repellent scenario as a result of limited wetting, with 70% of applied water draining rapidly via preferential flow paths, leaving much of the soil dry. We suggest that the predominant cause of the lower CO2 pulse in water-repellent soils was the smaller volume of pores in which the CO2 was replaced by infiltrating water, compared to wettable soil. This study shows that SWR should be considered as an important factor when measuring or predicting the CO2 flush upon rewetting of dry soils. Although this study focused mainly on short-term effects of rewetting on CO2 fluxes, the overall implications of SWR on physical changes in soil conditions can be long lasting, with overall larger consequences for C dynamics.